Unwanted pregnancy as a critical factor of stunting in Indonesia - Yanti, Linda; Supriyadi, Supriyadi; Santosa, Agus (Universitas Muhammadiyah Purwokerto, 2023)
Specific and sensitive nutrition fulfillment programs have been carried out to reduce the incidence of stunting in Indonesia, but the results are still not optimal. Handling stunting should not only focus on the nutrition fulfillment sector. A fundamental factor to consider as the root cause of high stunting in Indonesia is unwanted or unplanned pregnancies.